The Names of the Regions of Latvia and Lithuania in the Second Baltic Language - Kvašytė, Regina (Acta humanitarica academiae Saulensis, 2019)
The aim of the research is to find out the rendering and usage of Latvian and Lithuanian names of regions, singled out according to various criteria, in the second Baltic language. Dictionaries, encyclopaedias, press issues and information for tourists published in Lithuania and Latvia as well as other non-artistic texts, both written in Latvian or Lithuanian and translated into Latvian or Lithuanian, were chosen as sources for the investigation.The names of the five regions of Latvia, Kurzeme, Latgale, Sēlija, Vidzeme, Zemgale, are characteristic of quite diverse rendering and usage in the Lithuanian language. Systematically (and synchronically) assessing, the priority in giving a Latvian name of the region of Kurzeme the equivalent in Lithuanian Kuržemė as having a particular tradition of usage would be emphasised. However, recently, the growing popularity of the place name Kuršas in both historical and contemporary contexts is observed. Traditional and widespread equivalents are used in the following cases: the place name Vidzeme is rendered as Vidžemė and Latgale as Latgala; moreover, the usage of a Lithuanian equivalent Sėla being close to the name of the Latvian territory is suitable. A region of Southern Latvia, Zemgale, is most often named Žiemgala in Lithuanian. Nevertheless, in rare cases, other instances of the usage of these names, not always correct, were observed. As Latvian sources suggest, the rendering and usage of Lithuanian regions is much simpler. The most difficult name of the five regions, Aukštaitija, Dzūkija, Mažoji Lietuva, Suvalkija, Žemaitija, is the first one. Because of the difference in the consonants forming the basis of the root of the adjective having the same meaning (cf. Lithuanian aukštas and Latvian augsts), the forms Aukštaitija and Augštaitija were found; the form which is more similar to the original is the correct one. Both names Dzūkija and Žemaitija have no other variants differing from a Lithuanian form; and the name Suvalkija was used with a palatal consonant of the Latvian language, Suvaļkija, in one of the sources. Such rendering reflects pronunciation more precisely; however, still it has no tradition of being used. A complex name Mažoji Lietuva is usually translated word by word, Mazā Lietuva, even though, observing the analogy with other names of the same kind, it could be rendered by a compound Mazlietuva.The comparison of the names of regions demonstrates that the rendering of Latvian place names in Lithuanian and Lithuanian place names in Latvian is changing in both dictionaries and texts. Moreover, it is observed that it is difficult to render a Latvian word novads in Lithuanian, since it is used as both a synonym of a borrowing reģions and a name of a unit of territorial administrative division (in a spoken meaning, a Lithuanian equivalent nuovadas would be suitable).
Keywords: Latvia; Lithuania; proper names; place names; the names of the regions; rendering in Lithuanian; rendering in Latvian; usage